(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the artistic thinking and intertextual features of the short stories of Isajon Sulton, one of the prominent representatives of contemporary Uzbek prose. Based on thematic, intertextual, and stylistic methods of analysis, the writer’s artistic mastery and the ways in which layers of meaning are enriched through intertextual relations are examined on a scholarly basis. The findings of the study contribute to determining the place and significance of Isajon Sulton’s short stories within modern Uzbek literature.